Livelihood diversification and coping strategies: evidence from small-scale fish farmers in Ghana - Samuel Afotey Anang; Kwasi Otchere-Peprah; Daniel Aidoo-Mensah; Nicholas Oppong Mensah; Tekuni Nakuja; Dominic Boateng-Gyambiby (Cogent Social Sciences)
The study assessed livelihood diversification and coping strategies among small-scale fish farmers in the Nzema East Municipality, Ghana. Multistage sampling techniques comprising purposive sampling and snowball sampling were adopted to sample 200 fish farmers. The Simpson Diversification Index, Heckman’s two-stage regression model, and Tobit regression model were used for the data analysis. The results revealed that farmers had a very high perception that diversification increases their competitive advantage over other farmers who did not diversify with a weighted average index of 0.78. Again, fish farmers in the study area adopted many coping strategies to meet their family needs. Averagely, fish farmers in the area diversified approximately 52.8% of additional income sources into both non-agricultural and agricultural activities. Factors such as age, experience, and household size were found to have a negative effect on livelihood diversification, whereas farmer-based organization (FBO) membership, income level, and access to credit had a positive, significant effect on farmers’ livelihood diversification. Analysis of farmers’ coping diversification strategies revealed that factors such as gender, experience, and access to credit had a positive effect on the number of coping strategies adopted, while age and FBO membership had a negative correlation with the number of coping strategies adopted.